Historical Dictionary of Confucianism - Littlejohn, Ronnie L. (Rowman & Littlefield Publishers, 2023)
Historical Dictionary of Confucianismis devoted exclusively to Confucianism, the great Chinese tradition that has gathered around the teachings of Confucius (Kongzi) for more than 2,500 years. Confucianism encompasses a broad array of moral, social, philosophical and religious ideas, values and practices. It is an ancient and immense tradition of great subtlety and complexity. This work provides ready access to terms, personalities, movements, and texts of the tradition as it has made its trek throughout East Asia, especially Korea and Japan. This book contains a chronology, introduction, and extensive bibliography. The dictionary section has more than 700 cross-referenced entries on terms, personalities, movements, and texts of the tradition. Historical Dictionary of Confucianism is an excellent resource for students, researchers, and anyone wanting to know more about Confucianism.